"Nihil volitum nisi praecognitum": ¿siempre? - VALENTINI Y COLOMER, MANUEL (Anuario Filosófico, 2026)
The assertion that the natural movement of the will is preceded by an act of intelligence presents important difficulties. The analysis of a wide range of texts by Saint Thomas, prepared from a metaphysical perspective that understands the natural inclination of the will as the ontic tendency of the intellectual being towards the ultimate end, elucidates that the natural will originates from the habitual light of the agent intellect.